Analisis Kebutuhan Pengembangan Bahan Ajar Modul Hidroponik Berbasis Hasil Penelitian - Mellisa, Mellisa; Hajar, Ibnu; Herlina, Sari; Pebriani, Pebriani; Anthonia, Salshadilla (Perspektif Pendidikan dan Keguruan, 2024)
Teaching materials encompass all systematically organized content used in the learning process with the aim of illustrating the competencies that learners will acquire, including modules. The purpose of this research is to describe the results of the analysis of students' needs for teaching materials in the form of hydroponic modules based on research findings. The population in this study consists of students who have taken hydroponics courses. Sampling is done through simple random sampling, involving 31 students as research subjects. This descriptive research aims to determine the needs for the development of research-based module materials for hydroponics learning and to provide more optimal learning facilities. Research instruments include questionnaires for the needs of both teachers and students, observations, interviews, and documentation. The data analysis technique used is descriptive statistical analysis. Based on the research results, it can be concluded that students and teachers have a need for teaching materials that can broaden and enhance their understanding, and can be studied independently by students, especially in the form of research-based modules. This research is essentially an initial stage in the process of developing teaching materials in the form of modules based on research findings.